The constitution of Guyana : what will it look like???? - Parris, Haslyn (Trafford Pub. VictoriaCA, 2003)
Presents the actual and proposed constitutional amendments deriving from the Constitution Reform Commission's report. Provides therefore, a single document purporting to be the amended Constitution of Guyana, once all the recommended amendments have been approved.